Ethical communication in IT project from an Islamic perspective - Nizam, Mohamed; Aldossary, Alia Ahmed; Ibrahim, Jamaludin (2012)
Abstract—Interactive communication morals distinguish it from other methods of interaction morals by focused point for the association among information technology project team members. Official communications design is not focused in a minor portion of the information technology projects, and neither writing performance reports nor having a system of control over lessons learned frequent practices within organization. When the communication is not at the best relationship, interpersonal communication at all levels moves into another form of communicative interaction. The major objective of this paper is to identify the communicational obstacles and its impact on the information technology projects and suggest the best possible solution for these obstacles from the Islamic perspective. We assume that the knowledge that we pass through this paper would be beneficial for the future IT projects